Probing the Interaction of Diester Internal Donors (ID) with AlEt3 on Ziegler-Natta Surfaces: A Comparison Between Binary (MgCl2/ID) and Ternary (MgCl2/ID/TiCl4) Formulations - Felicia Daniela Cannavacciuolo; Giuseppe Antinucci; Roberta Cipullo; Vincenzo Busico (Molecules)
Organic electron donors are essential components of Ziegler-Natta (ZN) catalysts to produce isotactic polypropylene. In particular, aromatic or aliphatic diesters are widely used as ‘Internal Donors’ (ID) in MgCl2/ID/TiCl4 precatalyst formulations. Diesters are reactive with AlEt3 (by far the most common ZN precatalyst activator) and are partly removed from the solid phase in the early stages of the polymerization process; this is detrimental for catalyst functioning, and a surrogate donor (‘External Donor’ (ED), usually an alkoxysilane) is added to the system to restore performance. Recent studies, however, demonstrated that even in cases where most of the diester is extracted by AlEt3, the active sites retain a ‘memory’ of it in several aspects of the catalytic behavior (such as, e.g., the average productivity and the polydispersity index of the polymer produced). Considering that the residual diester is always in molar excess with respect to the active Ti, one may speculate that long-lasting interactions between the latter and diester molecules can occur. In turn, this should imply that the reactivity of AlEt3 is different with binary MgCl2/ID or ternary MgCl2/ID/TiCl4 mixtures. In this work, the latter hypothesis was explored for a library of diester IDs with large structural diversity. In line with the anticipation, the fractional amount of ID extracted by AlEt3 was generally lower for ternary mixtures, although to an extent exquisitely dependent on diester structure.